Maternal occupational exposure to asthmogens during pregnancy and risk of asthma in 7-year-old children: a cohort study. Issue 4 (11th April 2013) - Christensen, Berit Hvass; Thulstrup, Ane Marie; Hougaard, Karin Sørig; Skadhauge, Lars R; Hansen, Kirsten Skamstrup; Frydenberg, Morten; Schlünssen, Vivi
Abstract : Objectives: The objective of this study was to examine whether maternal exposure to asthmogens during pregnancy is associated with the development of asthma in 7-year-old Danish children, taking atopic status and sex into consideration. Design: The study is a prospective follow-up of a birth cohort. Setting and participants: A total of 41 724 women and their children from The Danish National Birth Cohort were categorised according to maternal occupational exposure. Exposure information was obtained by combining job title in pregnancy and 18 months after pregnancy with a commonly used asthma Job Exposure Matrix. Primary and secondary outcome measures: Primary outcome was parent-reported asthma among their 7-year-old children in an internet-based questionnaire. Secondary outcome was asthma among the same children with or without atopic dermatitis and among boys and girls, respectively. Results: Prenatal exposure to low molecular weight (LMW) agents was borderline associated with asthma in children with OR 1.17 (0.95 to 1.44) for children with atopic dermatitis and 1.10 (0.98 to 1.22) for children without. Maternal postnatal exposure was associated with asthma (OR 1.15 (1.04 to 1.28). After mutual adjustment, postnatal exposure (OR 1.13 (0.99 to 1.29) and the combined effects of prenatal and postnatal exposure (OR 1.34 (1.19 to 1.51)) seem to increase the risk of asthma in children. No significant associations were observed for other prenatal or postnatal exposures. The gender of the child did not modify the aforementioned associations. Conclusions: Maternal occupational exposures during pregnancy do not seem to be a substantial risk factor for the development of asthma in 7-year-old children. Maternal prenatal and postnatal exposures to LMW agents may predispose the propensity of the children to develop asthma. Future studies should prioritise the characterisation of the timing of exposure in relation to the birth.